THE ROLE OF ELECTRONIC MEDICAL RECORDS IN MEDICAL DISPUTE RESOLUTION: LEGAL REVIEW - Fauziah Nur; Bambang Fitrianto (PT. Radja Intercontinental Publishing, 2024)
Electronic medical records (RME) are important for increasing efficiency and accuracy in health services and facilitating the resolution of medical disputes by providing comprehensive and easily accessible documentation. However, the implementation of RME in Indonesia faces unclear regulatory challenges and data security issues. There is a need for harmonization of regulations to support the effective and safe implementation of RME, which can speed up the process of resolving medical disputes in a fair and transparent manner. This study aims to evaluate the regulations governing the use of electronic medical records (RME) in the health care system in Indonesia and assess their application in resolving medical disputes. Another aim is to identify the advantages and disadvantages of using RME in resolving medical disputes from a legal perspective. This research method uses a normative legal approach to analyze legal regulations related to electronic medical records and medical dispute resolution. Secondary data from various sources such as journals, books and legal articles are used for descriptive-analytical analysis. The research results show that regulations for the use of electronic medical records (RME) in Indonesia do not fully accommodate developments in RME technology, focus more on conventional medical records, and do not regulate aspects of data security, accessibility and interoperability of RME. Other challenges include data security and limited technological infrastructure in some areas. Compared with developed countries such as the United States (HITECH Act) and Europe (GDPR), Indonesia needs to update and harmonize regulations to support a more effective and safe implementation of RME in resolving medical disputes